INTERIOR DESIGN OF A COMMUNITY KITCHEN USING A USER ACTIVITY ANALYSIS APPROACH: A CASE STUDY OF FOODCYCLE INDONESIA - Dedrina Aurya Syazira; Ully Irma Maulina Hanafiah; Ira Wirasari (ADISAM Publisher, 2026)
A community kitchen is a collective space that serves not only for cooking activities but also as a venue for social collaboration and community empowerment. In the case of Foodcycle Indonesia, diverse activities and users with different backgrounds present challenges in designing spaces and furniture that are adaptable to user needs. This research employs a design thinking approach and qualitative methods to identify activity patterns and functional needs, as well as to develop spatial and furniture design strategies that support work efficiency and comfort. The study’s findings formulate a flexible design concept based on ergonomics and anthropometry to create an inclusive workspace that enhances the quality and comfort of activities within the community kitchen.